Reliability and validity of a return to sports testing battery for the shoulder. (March 2021) - Popchak, Adam; Poploski, Kathleen; Patterson-Lynch, Brittany; Nigolian, Jacob; Lin, Albert
Abstract: Objective: To determine the validity, intra- and inter-rater, and absolute reliability of a return to sport testing battery for the shoulder in a healthy cohort. Design: Cross-sectional design. All participants completed a battery of strength (isokinetic, isometric, and repetition to failure) and functional assessments on two occasions. Concurrent validity to isokinetic testing was assessed, and intra-rater, inter-rater, and absolute reliability were established for all assessments. Setting: Controlled clinical environment. Participants: Thirty healthy adults active in recreational sports participated, mean age 24.0 ± 1.6 years; Main outcome measures: Correlations (Pearson's r), reliability (Intraclass Correlation Coefficient), Standard error of the measurement, Minimal detectable change. Results: Correlations to isokinetic assessments at 60° & 180°/second were moderate to strong for isometric (r: 0.68–0.80) and functional testing (r: 0.55–0.83) and weak for repetition to failure testing (r: 0.37–0.74). All isokinetic (ICC: 0.88–0.94), isometric (ICC: 0.83–0.94), and functional assessments (ICC: 0.80–0.92) had good to excellent intra-rater reliability, while repetition to failure testing had poor to moderate reliability (ICC: 0.48–0.57). The inter-rater reliability of the isometric assessments was moderate to excellent (ICC: 0.71–0.92) across movements. Expressed as a percentage of the mean, the standard error of the measurement ranged from 7% to 25% and the minimal detectable change ranged from 20% to 69% across all assessment methods. Conclusion: The isokinetic, isometric, and functional assessments used in this return to sports testing battery demonstrates acceptable validity and reliability. Further refinement to the methods used to assess muscular endurance is needed to improve reliability. This study offers clinicians information that can be utilized in clinical decision-making as it relates the testing battery's psychometric properties.